The divine conspiracy : rediscovering our hidden life in God - Willard, Dallas, 1935-2013 (HarperSanFrancisco, 1998)
Presents a revolutionary way for Christians to experience God, challenging readers to follow the teachings of Christ to embrace the true meaning of Christian discipleship.